Study of chip shape and surface finish in ultra-precision machining - Foo, Jong Chien. (2009)
In this work, ultra-precision machining on aluminum alloys were carried out to investigate the surface quality using single point diamond tools (SPDT) cutters. Examined by SEM, the machined surfaces took on many defects such as microcracks, pits, voids or even scratches. It was found out that the cutting parameter such as feed rate and the usage of different workpiece materials had a significant effect on the surface quality when ultra-precision machining these aluminum alloys. The results showed that surface finish quality got worse with increasing feed rate or using a less hard material. The purpose of this study is to show that even if ultra-precision machining at low feed rate is carried out, there will still be defects which affect the surface finish quality. Investigation of chip formation would be carried out in this work for the study of the chip geometry. The results showed that the increase in the depth of cut would create thinner deformed chips. Comparison of the theoretical and experimental shape of the chip would also be made in this project. The decision of selecting a suitable machining parameter always depends on surface finish, part machinability and part geometry. An understanding of the results from SEM together with the relationship between machining parameter and surface finish can lead to improved control over the process, which is a vital consideration for ultra-precision machining.